The Effect Modification of Pregnancy Mother's Class on Parent Readiness on Primigravida at Upt Puskesmas Beber, Cirebon Regency in 2022 - Suratmi Suratmi; Nina Nirmaya Mariani (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Becoming a parent is a very important phase of life for humans and has a big impact if one goes wrong in the process. Therefore, various efforts are needed so that every couple has the readiness to become parents. On the other hand, Class for Pregnant Women (KIH) is a program aimed at making mothers aware of all information and as a means to learn together about health for pregnant women, in the form of face-to-face in groups. It is necessary to modify the KIH in order to prepare to become a maximum family. The study was conducted at Beber Health Center, Cirebon Regency from March to December 2022 with a quasi-experimental quantitative study in one group (non-random pre-test and post-test without control group design). Sampling was carried out by Total Sampling on the mother of the first child as many as 28 respondents. The activity was carried out 4 times in an attractive manner and got the results that most of the respondents were aged 20-35 years, had elementary school education, did not work, the average score of readiness before the intervention was 34.29 (± 5,437) and before the intervention was 41.67 (± 4,977). there is a difference in the average readiness as a parent before and before the intervention with a p value of 0.001. Based on this research, the Maternity Class with modifications needs to be developed and implemented for mothers of the first child to increase readiness as parentKeywords:  Modification, KIH, Being, Parent